Buckling of Radially Loaded Concrete Cylinders in Fire Condition - Abdelraouf Tawfik Kassem (Salehan Institute of Higher Education, 2019)
Concrete cylinders are commonly used in water treatment and sewerage plants, in the form of wells or basins. They are mainly subjected to axial compression resulting from soil lateral pressure and aqueous hydrostatic pressure, in case of the presence of a groundwater table; that is why they are mostly designed in the form of a circular hollow section. Concrete cylinders face a complicated case of loading in fire condition, as a result of material degradation in addition to thermally induced stresses. This paper studies buckling stability of that case where, a concrete cylinder is subjected to an internal fire load in addition to superimposed structural loads from the surrounding environment. The main objective of the research is to study buckling stability of concrete cylinders through identifying various structural and thermal parameters, controlling that behaviour. Finite element modelling using